2020
DOI: 10.22458/urj.v12i2.3033
|View full text |Cite
|
Sign up to set email alerts
|

The video as a tool to change perceptions and knowledge about snakes in adults with a high academic level in Costa Rica

Abstract: Introduction: Snakes suffer persecution by humans for misperception, misinformation, and fear. In addition, snakes are threatened by habitat decline, which leads them to seek new territories, favoring human-snake encounters. In Costa Rica these threats also exist in the inhabitants of the city, even in those with a high academic level. To favor the conservation of snakes, it is necessary to implement environmental education strategies aimed at a specific target audience. One possible tool is the creation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A few studies also looked at fear and disgust of snakes as evolutionary or taught responses, hypothesising that those who feared snakes the most also had trouble correctly identifying them ( Henke et al, 2019 ) and were less likely to absorb corrective information ( Castillo-Huitrón et al, 2020 ). One study concluded that using audio-visual aids can be effective in changing the perception of people about snakes ( Quesada-Acuña and Pérez-Gómez, 2020 ), though the sample size was limited. These studies are highly pertinent since snakes occupy a unique position among dangerous wildlife of being present in both urban and rural human-dominated landscapes and have one of the highest mortality rates of humans caused by any dangerous wildlife species ( Tumram et al, 2017 ; Conover, 2019 ).…”
Section: Promoting Co-existence With Venomous Snakes: Evaluating Mitigation Methods For Human-snake Conflictmentioning
confidence: 99%
“…A few studies also looked at fear and disgust of snakes as evolutionary or taught responses, hypothesising that those who feared snakes the most also had trouble correctly identifying them ( Henke et al, 2019 ) and were less likely to absorb corrective information ( Castillo-Huitrón et al, 2020 ). One study concluded that using audio-visual aids can be effective in changing the perception of people about snakes ( Quesada-Acuña and Pérez-Gómez, 2020 ), though the sample size was limited. These studies are highly pertinent since snakes occupy a unique position among dangerous wildlife of being present in both urban and rural human-dominated landscapes and have one of the highest mortality rates of humans caused by any dangerous wildlife species ( Tumram et al, 2017 ; Conover, 2019 ).…”
Section: Promoting Co-existence With Venomous Snakes: Evaluating Mitigation Methods For Human-snake Conflictmentioning
confidence: 99%